Digital Literacy in Medical Education: Strengths, Gaps, and the Way Forward - Humaira Shamim; Nomira Waheed; Zunaira Azher; Hammad Karim; Fatima Abid; Saba Iqbal (Pakistan Journal of Health Sciences, 2026)
Digital transformation of healthcare has transformed clinical practice, medical education, and professional competencies around the world. Digital literacy includes technological skills, ethical use, artificial intelligence (AI), and cybersecurity. It is now regarded as a safe, effective, and future-ready healthcare practice. Despite increased exposure to digital tools, evidence reveals that healthcare students may lack structured capabilities in new digital domains. Objectives: To evaluate the level of digital literacy among undergraduate medical and dental students and identify domain-specific strengths and gaps, particularly in emerging areas such as artificial intelligence and cybersecurity. Methods: An analytical cross-sectional study was conducted using a validated 24-item self-report instrument. The survey measured seven domains of digital literacy using a 5-point Likert scale. A total of 304 MBBS and BDS students participated. Data were analyzed using SPSS v26, applying descriptive statistics, t-tests, and Spearman’s correlation. Results: Among the participants, 77.6% were MBBS students and 22.4% were from BDS, with 60.9% females and 39.1% males. No significant gender-based differences were found in any digital literacy domain. First-year students scored significantly higher in the digital security domain than second-year students (p=0.002). Overall, students demonstrated moderate digital literacy, with comparatively lower scores in AI and cybersecurity domains. Conclusions: While digital literacy is generally consistent across gender and academic levels, low competency in AI and cybersecurity signals an urgent need for targeted curricular interventions. Integrating digital literacy, especially AI and data security, into undergraduate curricula is essential for preparing future-ready healthcare professionals.